2013
DOI: 10.4081/hpr.2013.e29
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and religion in pain and pain management

Abstract: Pain relief is a management problem for many patients, their families, and the medical professionals caring for them. Although everyone experiences pain to some degree, responses to it vary from one person to another. Recognizing and specifying someone else’s pain is clinically a well know challenge. Research on the biology and neurobiology of pain has given us a relationship between spirituality and pain. There is growing recognition that persistent pain is a complex and multidimensional experience stemming f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…Various studies support that the presence and severity of neuropathic pain are associated with greater impairments in quality of life. However, as this impact varies somewhat as a function of the domain being considered (17), a finer analysis of quality of life domains must be considered in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies support that the presence and severity of neuropathic pain are associated with greater impairments in quality of life. However, as this impact varies somewhat as a function of the domain being considered (17), a finer analysis of quality of life domains must be considered in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that many individuals rely on their spirituality and faith when coping with stres in most cultures. (16)(17)(18)(19)(20) Dedeli & Kaptan (13) indicated that people apply cognitive and behavioral strategies including religion/spirituality to cope with pain. Another study showed religious-spiritual coping can be very helpful when dealing with chronic disease.…”
Section: Dıscussıonmentioning
confidence: 99%
“…In Islam, it can be punitive or Allah's will. (13) Being Muslims, they often believed that illness and injury are caused by a higher power (Allah) and they offered their illness, injury, pain, and suffering to Allah in thanks for the good fortune of being allowed the special medical or/and surgical treatments. (14) The sample in this study of spiritual practices consists of persons who were predominantly Muslim and had come from an Islamic background.…”
Section: Dıscussıonmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramirez showed that the positive religious coping was related to psychological health and quality of life in patients undergoing hemodialysis (15). Dedeli indicated that people apply cognitive and behavioral strategies including religion/ spirituality to cope with pain (16). Akbari demonstrated that religion creates hopefulness, compensates for negativism and increases happiness in people.…”
Section: Introductionmentioning
confidence: 99%